Diagnosis National Mobilization for Reading Comprehension: Modules 1, 2 and 3 - Inga Arias, Miguel Gerardo (2014)
This paper presents an assessment of the need for more serious proposals MINEDU has worked to overcome the serious problems in terms of reading comprehension are presented in Peruvian education: the modules of the National Mobilization for Reading Comprehension, which has been taking out since 2009. This mobilization has ensured that all students in the country are required readings for classroom work, which have been selected and adapted according to the multicultural reality of our country. This research allowed us to evaluate the implementation of these modules through the use of surveys to a representative sample of Peruvians educational institutions (Lima, La Libertad, Moquegua, Junin, Huanuco, San Martin and Madre de Dios). These information gathering tools were applied to teachers and students, which were then contrasted with the Classroom Observation Form. Through them are evident weaknesses, strengths and opportunities of education agents. Therefore, subsequent to such surveys and classroom observation of teaching performance, were conducted workshops according to the needs of each group and personal conductive to everybody involving even learning sessions we developed some classrooms. Finally, conclusions and suggestions, many of them incorporated in subsequent directives instances. These permit to make the necessary and urgent adjustments in teacher training and in the efficient and effective reading comprehension modules.